2020
DOI: 10.1186/s13102-020-00210-y
|View full text |Cite
|
Sign up to set email alerts
|

Flywheel squats versus free weight high load squats for improving high velocity movements in football. A randomized controlled trial

Abstract: Background High load (HL: > 85% of one repetition maximum (1RM)) squats with maximal intended velocity contractions (MIVC) combined with football sessions can be considered a relevant and time-efficient practice for maintaining and improving high velocity movements in football. Flywheel (FW) resistance exercise (RE) have recently emerged with promising results on physical parameters associated with football performance. Methods In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 56 publications
6
41
0
Order By: Relevance
“…Although this type of practice is very popular in the last decades [13], scanty studies have compared the effects of flywheel and traditional weight training on performance in athletic population [17,19,37], and generally presented data similar to our study findings. In a six week study by Maroto-izguierdo et al [19], 15 flywheel training sessions (4 × 7 maximal intensity half squats done with 0.145 kg•m 2 moment inertia) produced superior improvements (p < 0.05-0.001) compared to traditional weight training (4 × 7 leg presses with load corresponding to 7 repetitions maximum (7 RM) for each set) for vertical jump (9.8% vs. 3.4%), change of direction ability (−7% vs. −4.4%) but also 20 m sprint time (−10% vs. −5.1%) in professional handball players.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although this type of practice is very popular in the last decades [13], scanty studies have compared the effects of flywheel and traditional weight training on performance in athletic population [17,19,37], and generally presented data similar to our study findings. In a six week study by Maroto-izguierdo et al [19], 15 flywheel training sessions (4 × 7 maximal intensity half squats done with 0.145 kg•m 2 moment inertia) produced superior improvements (p < 0.05-0.001) compared to traditional weight training (4 × 7 leg presses with load corresponding to 7 repetitions maximum (7 RM) for each set) for vertical jump (9.8% vs. 3.4%), change of direction ability (−7% vs. −4.4%) but also 20 m sprint time (−10% vs. −5.1%) in professional handball players.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, lower body strength increased significantly and similarly in both groups. Finally, effects of flywheel and traditional strength training on 10-m sprint, cmJ and lower body strength (1 RM squat) were examined on 38 active male football players by Sagelv et al [37]. During six weeks of intervention (2 sessions per week), both flywheel and traditional strength training progressively increased squat exercise from 3 sets with 6 repetitions (week one) to 4 sets with 4 repetitions (week six).…”
Section: Discussionmentioning
confidence: 99%
“…Participants in 8 of the 11 studies included elite academy soccer players (Fiorilli et al, 2020;Gonzalo-Skok et al, 2019;De Hoyo et al, 2015Nuñez et al, 2019;Raya-González et al, 2021a;Suarez-Arrones et al, 2018;Tous-Fajardo et al, 2016). The remaining studies included players from 2 professional Swedish premier league teams (Askling et al 2003), 2 semi-professional (Serie D) soccer teams (Coratella et al, 2019) and 38 recreational players from the fifth and sixth tier of the Norwegian National League (Sagelv et al, 2020). In the 11 selected studies, volume ranged from 1 to 6 sets of 5-10 repetitions with frequency varying from 1 to 2 sessions a week.…”
Section: Supplement/ Ergogenic Aidsmentioning
confidence: 99%
“…m 2 (Coratella et al, 2019;Gonzalo-Skok et al, 2019;De Hoyo et al, 2015;Raya-González et al, 2021a;Sagelv et al, 2020;Suarez-Arrones et al, 2018;Tous-Fajardo et al, 2016), while the inertia used in the remaining studies was not reported (Askling et al 2003;Fiorilli et al, 2020;De Hoyo et al, 2015Nuñez et al, 2019). Eight of the eleven studies followed a progressive programme, gradually increasing training volume or intensity over the intervention period (Coratella et al, 2019;De Hoyo et al, 2015Nuñez et al, 2019;Raya-González et al, 2021a;Sagelv et al, 2020;Suarez-Arrones et al, 2018;Tous-Fajardo et al, 2016). Finally, five studies individualized intensity by selecting inertias reporting the highest power outputs (De Hoyo et al, 2015Nuñez et al, 2019;Sagelv et al, 2020;Suarez-Arrones et al, 2018).…”
Section: Supplement/ Ergogenic Aidsmentioning
confidence: 99%
“…Flywheel inertial resistance exercise received attention in recent years due to its many positive effects on athletic performance variables (change of direction, jumping, and sprinting) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] and injury prevention in sport [ 8 , 9 , 10 ]. Robust (large and rapid) improvements in muscle strength and power could be attributed to neurological adaptations [ 11 , 12 , 13 , 14 ], morphological adaptations [ 15 , 16 , 17 , 18 , 19 ], or the sum of both, depending on the duration of the training protocol [ 20 ] and, presumably, the magnitude of the (flywheel) FW load selected.…”
Section: Introductionmentioning
confidence: 99%